Reflective writing in pharmacy practice - Jamshed, Shazia Qasim; Shamsudin, Siti Hadijah (Wiley-Blackwell, 2014)
Pharmacists, being health information gurus and one of the largest groups of healthcare providers, seep into the changing dynamics of the healthcare environment where now the patient is both demanding of, and receptive to, information even on minor illnesses. The profession of pharmacy holds the concept of ‘patient centred care,’ thus shifting the image of a pharmacist from a dispenser to a decision-maker and caregiver. This places an additional burden on the pharmacist, and therefore the practice of professional principles should be more dynamic and action-oriented in the best interest of the patient. Future pharmacy practitioners need to gain better understanding of the professional principles and heterogeneous philosophies of pharmacy practice that initiate from dispensing, counselling, congenial interprofessional and intra-professional working, and later culminate in drug and patient safety, pharmacogenomics and pharmacoinformatics. In order to accomplish this, future pharmacy practitioners could be frequently acclimatized to the concept of reflective learning in different pharmacy modules. It is suggested that the concept of reflective learning could be nurtured by observational writing. The requirement of reflection-imbued observational writing generally, exposes the students to activities related to learning and makes them an insider for a transient epoch facilitating in facing the world being observed.